Den fysiska modellen som kommunikationsverktyg för praktiserande landskapsarkitekter - Doms, Camilla (2018)
With the mounting introduction of digital drawing and modelling tools into the architectural industry, the tradition of constructing physical models has been phased out. Landscape architects build digital models in order to examine their design suggestions but it is rare for them to use them as a form of communication. Making the physical model comparable to its digital counterpart, or even entirely substituting the former with the latter, causes the landscape architect to lose an opportunity of communicating spatial design through a three-dimensional medium. In this study, the physical model has once again been inserted into the selection of communication tools at the disposal of five practicing landscape architects. Through qualitative interviews it examines how they experience the physical model as a means of conveying their proposed designs. The results of this study leads to the conclusion that practicing landscape architects treat the physical model both as a process and a static device; they regard it as both a tool for generation and communication of ideas. The underlying reason why landscape architects tend not to utilise the physical model as a means of communicating their designs is that it is not seen as a part of their “standard” inventory of tools with that purpose. Instead, they feel that it is superfluous, insufficient, inconvenient, insecure and economically wasteful to work with. In order to increase the usage of the physical model amongst landscape architects, efforts should be made to counter these negative experiences and preconceived notions. On the other hand, it cannot be assumed that the physical model has an obvious place within the array of tools that landscape architects use to communicate, as it is broadly thought of as a powerful medium but still frequently rejected in favour of digital alternatives.